Implementation of Responsibility Accounting with Budget as a Cost Control Tool at PT. Varia Usaha Fabrikasi - Diana, Eva Nur; Hariyono, Anwar (Indonesian Vocational Research Journal, 2023)
This study explores the application of responsibility accounting with budgets as a cost control tool at PT. Varia Usaha Fabrikasi. As a labor service provider company, PT. Varia Usaha Fabrikasi has a strategic role in supporting Indonesia’s economic growth. By describing conditions before and after the Covid-19 pandemic, this study identifies economic growth opportunities and company demands to take advantage of the technological era 4.0. The literature review presents the concept of responsibility accounting, characteristics, requirements, and the role of budget as a cost control tool. A conceptual framework was conceived as a theoretical foundation for the study. Previous research noted that the implementation of budget accounting accountability at PT. HearLIFE Indonesia still needs improvement. The research method used is qualitative with a case study approach at PT. Varia Usaha Fabrikasi. Data is obtained from interviews, observations and analysis of company documents. The results of data analysis show that PT. Varia Usaha Fabrikasi has met the requirements of liability accounting, including a clear organizational structure, cost segregation, classification of account codes, and cost reporting systems. The budgeting process at PT. Varia Usaha Fabrikasi involves the participation of each department, and its implementation includes effective monitoring and control. Analysis of cost variance in 2020-2022 shows both favorable and unfavorable results, gives a comprehensive picture of budget realization. This research contributes to the understanding of responsibility accounting practices and the application of budgets as a cost control tool in the context of labor service provider companies. These findings are expected to provide insight into similar companies and researchers in the field of management accounting.